Not just for mature audiences: myeloproliferative neoplasms in children, adolescents, and young adults - Resar, Linda; Jain, Tania (Frontiers in Hematology, 2025)
Myeloproliferative neoplasms (MPNs) are chronic, clonal blood disorders characterized by overproduction of mature blood cells. MPNs present with protean clinical manifestations, including vascular complications, with both venous and arterial thromboses, bleeding diathesis, which occur in the setting of extreme thrombocytosis and acquired von Willebrand disease, and an increased risk of transformation to acute myeloid leukemia (AML). While previously diagnosed primarily in middle-aged and older adults, MPNs are increasingly being recognized in children and young adults. Indeed, studies of clonal evolution trace the development of MPN driver mutations to in utero in some cases. However, prior diagnostic criteria and treatment guidelines have evolved primarily from studies of older MPN patients. Thus, research focused on MPN in younger patients is warranted. Here, we review prior studies of clinical manifestations, outcomes, and therapy for younger patients with MPN.